POPULARIZATION OF PRIVATE DETECTIVE PRACTICE IN THE MEDIA - Rimanas, Oļegs (Administrative and Criminal Justice, 2017)
The article briefly examines the 10-year positive experience of JSC Rimano biuras (Lithuania) in promoting the activities of private detectives in the main forms of periodic dissemination of mass information, for mutually beneficial cooperation with journalists.